2002
DOI: 10.1182/blood.v99.10.3623
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the von Willebrand (VWF)–collagen interaction by an antihuman VWF monoclonal antibody results in abolition of in vivo arterial platelet thrombus formation in baboons

Abstract: The interaction between collagen, von Willebrand factor (VWF), and glycoprotein Ib is the first step in hemostasis and thrombosis especially under high shear conditions. We studied the inhibition of the VWF-collagen interaction by using an antihuman VWF monoclonal antibody 82D6A3 to prevent arterial thrombosis in baboons to develop a new kind of antithrombotic strategy and determine for the first time experimental in vivo data concerning the importance of the collagen-VWF interaction. We used a modified Folts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 20 publications
5
82
0
1
Order By: Relevance
“…We recently demonstrated that inhibiting the VWF-collagen interaction by 82D6A3 results in an effective antithrombotic therapy when tested in baboons using a modified Folts model in the femoral artery (33), thereby confirming that the VWF-collagen interaction has a relevant physiological role.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We recently demonstrated that inhibiting the VWF-collagen interaction by 82D6A3 results in an effective antithrombotic therapy when tested in baboons using a modified Folts model in the femoral artery (33), thereby confirming that the VWF-collagen interaction has a relevant physiological role.…”
Section: Discussionmentioning
confidence: 95%
“…We raised a monoclonal antibody (mAb), 82D6A3, against human VWF that prevents the binding of VWF to collagen (24) and that is antithrombotic in a baboon arterial thrombosis model (33). Since a previous effort to determine the epitope of 82D6A3 using phage display, was not successful (34,35), we repeated this study using less stringent selection criteria.…”
mentioning
confidence: 99%
“…The VWF-collagen interaction is a potential target for therapeutic intervention (41). Our crystallographic data reveal that although the VWF-binding site overlaps those of DDR2 and SPARC marked differences exist suggesting it should be possible to specifically block the VWF-binding site on collagen.…”
Section: Discussionmentioning
confidence: 97%
“…Surprisingly, these mutations caused no (32) or only moderate (33) bleeding symptoms, which questioned the relevance of the A3 domain for immobilization of VWF to the vascular matrix (32). However, Wu et al (34) recently showed that collagen binding by the A3 domain is relevant because an antibody blocking the VWF-A3-collagen interaction prevented the formation of platelet-rich thrombi and prolonged the skin bleeding time at high doses. Further investigations are required to reconcile these conflicting observations and to establish the physiological importance of VWF-A3 in platelet adhesion.…”
Section: Discussionmentioning
confidence: 99%